Assessing Impact of Goals by Foreign Players on Football Match Outcomes using Poisson and Ordered Logistic Regression Models: An Evidence from Thailand Premier League - Wichitaksorn, Nuttanan; Wongjirasak, Sardtarin; Tharisung, Kaesinee (Journal of Applied Statistics and Information Technology, 2022)
Foreign football players have been widely accepted for their competitive and complementary effects on the success of both national and club levels. This study investigates the contributions from the goals scored by the foreign players in the Thailand premier league, which is a top-eight league in Asia. Using the match- level data, the goals by foreign players have a strong and positive impact on the match outcomes either as the team's total number of goals or the win-draw- lose results. In addition, home advantage also has the considerable positive and negative effects, respectively on the match outcomes. The similar analysis is also performed for the case of goals by local players and reveals the complementary effect of the goals by foreign players.